2012
DOI: 10.1111/cmi.12028
|View full text |Cite
|
Sign up to set email alerts
|

From single-strand breaks to double-strand breaks during S-phase: a new mode of action of theEscherichia coli Cytolethal Distending Toxin

Abstract: SummaryThe Cytolethal Distending Toxin (CDT) is a genotoxin produced by several pathogenic bacteria. It is generally admitted that CDT induces double-strand breaks (DSB) and cell cycle arrest in G2/M-phase, in an ATM-dependent manner. Most of these results were obtained at high dose (over 1 mg ml -1 ) of CDT and late after treatment (8-24 h). We provide here evidence that the Escherichia coli CDT (EcCDT) -at low dose (50 pg ml -1 or LD50) and early after treatment (3-6 h) -progressively induces DNA DSB, mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 62 publications
6
103
0
Order By: Relevance
“…This subunit is functionally and structurally homologous to mammalian DNase I, and causes DNA strand breaks once internalised within the nuclear compartment [13][14][15][16].…”
Section: Bacterial Genotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This subunit is functionally and structurally homologous to mammalian DNase I, and causes DNA strand breaks once internalised within the nuclear compartment [13][14][15][16].…”
Section: Bacterial Genotoxinsmentioning
confidence: 99%
“…16 internalization, considering that the OMVs-mediated delivery offers several advantages such as: i) protection from extracellular proteases, increasing thereby the half life and allowing intoxication of distant targets; ii) delivery of higher toxin concentration to a specific destination, decreasing thereby the effective amount that needs to be produced, thus saving energy (reviewed in [53,54]). Thus, this issue deserves further investigations.…”
Section: Translocation To the Nucleusmentioning
confidence: 99%
“…This observation was confirmed in the mammalian system by Fedor et al, who demonstrated that iRNA knockdown of RAD51 in HeLa cells strongly promotes cell death upon exposure to EcolCDT [57]. While the study in S. cerevisae could not conclusively demonstrate a contribution of the NHEJ repair pathway to the CdtB-induced DNA lesion [142], Fahrer et al provided evidence that both HR and NHEJ protect cells from DNA lesions induced by HducCDT [143].…”
Section: Ddr Activation Upon Cdt Intoxicationmentioning
confidence: 88%
“…More recently, Fedor and colleagues have performed a detailed kinetics analysis of the CDT-induced DNA lesions and demonstrated that low doses of EcolCDT-I (50 pg/ml) at early points in time after toxin exposure (3-6 h) induces DNA single strand breaks (SSBs), which are further converted into DNA double strand breaks (DSBs) in the S phase of the cell cycle due to the inhibition of the progression of the replicative fork as a consequence of unrepaired SSBs [57]. Conversely, in the same time frame, higher toxin doses (above 75 ng/ml) induced the formation of DSBs, possibly due to the exceeding formation of SSBs on opposite strands, independently of the cell cycle phase.…”
Section: Enzymatic Activitymentioning
confidence: 99%
“…In yeast, homologous recombination is the predominant DNA repair mechanism for protection against CDT-induced lesions [42], whereas in human cells, both HR and NHEJ repair pathways protect against CDT-induced DSBs [40]. At low doses, CDT primarily generates SSBs which are converted into DSBs during the S-phase [43,44]. It was recently shown that chronic exposure to CDT could induce genomic instability in rat fibroblasts andcolorectal carcinoma cell lines [44].…”
Section: Cdt Bacterial Dnase Targets the Eukaryotic Genomementioning
confidence: 99%